Trick or treat! How to reduce co-destruction behavior in tourism workplace based on conservation of resources theory?. (September 2022) - Guan, Xinhua; Gong, Jinhong; Huan, Tzung-Cheng
Abstract: In the tourism industry, the phenomenon of value co-destruction is not uncommon, and it has become a stumbling block to the healthy and rapid development of the tourism industry. Based on the conservation of resources theory, this research explores the mechanism of the impact of organizational inducement on value co-destruction behavior in the workplace. Through a questionnaire survey of 624 frontline employees of tourism companies, this study finds that organizational inducement not only enhances the service rule commitment of employees but also helps reduce value co-destruction behavior in the workplace, service rule commitment mediates the buffering effect of organizational inducement on value co-destruction behavior in the workplace, and relational energy negatively moderates the impact of organizational inducement on service rule commitment. The findings of the study provide enlightenment on the most efficient measures an enterprise takes under the condition of limited resources.